In Search of Durable Solutions for Refugees in Indonesia: A State Security and Human Rights Protection Approach - Syahrin, M. Alvi; Qalandy, M. Rafly; Jafizhan, M. Syaran (The Age of Human Rights Journal, 2024)
The Indonesian government is experiencing difficulties in dealing with the refugee problem. This is because the number of refugees in the waiting period is increasing and the destination country limits the acceptance quota. Currently, the refugee problem in Indonesia is regulated in Presidential Regulation No. 125/2016. However, its implementation has not been optimal, as it is hampered by coordination and legal compliance factors. The implementation of the Presidential Regulation creates inconsistencies in legal norms with other regulations. Then, some local governments have begun to reject the presence of refugees. They are not willing to prepare shelters for refugees, because it burdens the budget. Currently, the government does not have a long-term solution that can be used to solve the refugee problem in Indonesia. This paper will discuss Indonesia’s role in solving the refugee problem by formulating strategic policies from a humanitarian perspective. This article uses socio-legal research with a qualitative approach. Although not a state party to the 1951 Convention, Indonesia has adopted various international laws that protect the human rights of refugees. However, its legal legitimacy is still disputed from the perspective of state security and sovereignty. Indonesia continues to be encouraged to ratify the convention to strengthen the promotion and defense of refugee rights. In fact, ratification can be a quick way to bridge the gap between international and domestic legal frameworks in addressing refugee issues in Indonesia. However, the government cannot wait to resolve this issue until the convention is ratified. There are several long-term solutions that can be practiced to address the refugee issue, including: pushing for human rights instruments to implement the basic rights of refugees; re-establishing the refugee issue as part of the National Human Rights Action Plan; revising Presidential Regulation No. 125/2016; and formulating a new policy with Indonesia, UNHCR, and giving greater authority to IOM to empower refugees while they wait to enter the destination country.